Exploring potential in participation mediated by digital technology among older adults. Issue 3 (3rd July 2017) - Fischl, Caroline; Asaba, Eric; Nilsson, Ingeborg
ABSTRACT: Facets of participation have changed with the growing pervasiveness of digital technology in daily life. To enable older adults as active participants in an evolving digital society, it is relevant to examine how they engage in and situate digital technology-mediated occupations in daily life. Narrative inquiry was used to elucidate features in older adults' engagement in occupations involving digital technology situated in everyday life. Analysis was based on data gathered through concurrent think aloud protocol and observations from 10 older adults in Northern Sweden. In line with narrative analysis, findings were presented as three stories about negotiating needs and values while interacting with the technological and social environments, entitled playing by the rules, being on the same wavelength, and calling the shots . Looking at these stories with an occupational lens resulted in an understanding that older adults' participation involving digital technology likewise deals with negotiating and refining identities, as well as finding and experiencing meaning in daily life. There is potential for older adults to become active participants through digital technology, and new challenges in research and practice emerge.